Penyelesaian Sengketa Pajak melalui Keberatan dan Banding - Khalimi Khalimi (Jurnal Penelitian Hukum Legalitas, 2017)
The purpose of this study is to identify the possibility of the parties to the dispute in an effort to win the tax dispute case. Analysis of the parties to the dispute in winning the tax dispute case is expected to identify the taxpayer. This study uses juridical normative research with the approach of this research law to examine efforts to resolve tax disputes in Indonesia. The results of this study found that an alternative tax dispute resolution is needed to resolve the above problems, such as mediation of tax disputes conducted by an independent party. Therefore, the researcher suggests that it is necessary to create a Tax Dispute Resolution and Mediation Institution which is a non-ministerial government agency whose duty is to handle complaints and be an independent mediator of the tax dispute between the taxpayer and the Directorate General of Taxes.